Detection of orthopaedic implants and in vitro objects using hand held metal detector - Khan, Rizwan (2021)
Background: Hand held metal detector (HHMD) is used in the MRI environment of many hospitals, which is not appropriate to prevent MRI hazards. The objective of this study is to assess the diagnostic accuracy of the HHMD in detecting in vitro objects and the associated factors involved in detection of orthopaedic implants within patients. Materials and Methods: This is a cross-sectional study conducted in Radiology Department, HUSM from October 2018 to June 2019. In the first phase of the study, 180 orthopaedic patients of age 18 years and above, operated in HUSM who came to the orthopaedic clinic for follow-up, were scanned using HHMD, and findings were recorded. Patients were categorised into obese and non obese, using body mass index. Implants details (dimension and site) were obtained from the patient’s operative notes. In the second phase, 164 in vitro objects (ferromagnetic and non ferromagnetic) were scanned using HHMD, and findings were recorded. Pearson chi-square test was used to determine the factors (obesity status and site of implant) associated with the detection of orthopaedic implants in patients using HHMD (in vivo). The sensitivity, specificity, and accuracy of the HHMD in the detection of ferromagnetic and non ferromagnetic objects (in vitro) were calculated using standard formulas. Results: One hundred seventy five (97.2%) of the 180 implants were detected by the HHMD. The overall rate of detection was 100% for arthroplasty implants and 100% for plates. 94.1% of screws were detected. Only 60% of K wires were detected. 100% of titanium and 95.5% of stainless steel orthopaedic implants were detected. Two implants in each range <50 mm and 51-100 mm and one implant in the range 101-150 mm were not detected. Other orthopaedic implants were detected regardless of size. Obesity and site of orthopaedic implants did not show association with detection of orthopaedic implants in patients using HHMD (P = 1.000 and P = 0.158). Overall sensitivity, specificity, and accuracy of HHMD in detecting ferromagnetic objects were found to be 96.3%, 73.2%, and 84.8% respectively. Conclusion: All joint prostheses, nails, and plates were detected by the HHMD. Few screws and K wires were not detected. All titanium implants were detected and a small number of stainless steel implants were not detected. Obesity and site of orthopaedic implants were not significant factors in HHMD detection. HHMD was not accurate in detecting ferromagnetic and non ferromagnetic objects.